2021
DOI: 10.3390/ijms221910515
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of TMEM175 Lysosomal Potassium Channel to the Plasma Membrane by Dynasore Compounds

Abstract: TMEM175 (transmembrane protein 175) coding sequence variants are associated with increased risk of Parkinson’s disease. TMEM175 is the ubiquitous lysosomal K+ channel regulated by growth factor receptor signaling and direct interaction with protein kinase B (PKB/Akt). In the present study, we show that the expression of mouse TMEM175 results in very small K+ currents through the plasma membrane in Xenopus laevis oocytes, in good accordance with the previously reported intracellular localization of the channel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…Our study identified several rare non-synonymous TMEM175 , TMEM163 , and TMEM229B variants, but no association of these genes with PD was found. TMEM175 is a component of a lysosomal K + channel, and its deficiency results in impaired lysosomal and mitochondrial function ( Jinn et al, 2017 ; Pergel et al, 2021 ). Variants of TMEM175 have been identified to be associated with PD in a GWAS study, indicating its role in PD ( Nalls et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified several rare non-synonymous TMEM175 , TMEM163 , and TMEM229B variants, but no association of these genes with PD was found. TMEM175 is a component of a lysosomal K + channel, and its deficiency results in impaired lysosomal and mitochondrial function ( Jinn et al, 2017 ; Pergel et al, 2021 ). Variants of TMEM175 have been identified to be associated with PD in a GWAS study, indicating its role in PD ( Nalls et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…TMEM175 currents in the plasma membrane were greatly increased in the cells treated with dynasore, with an estimated EC 50 of at least 30 µM [88]. Dyngo-4a, a hydroxylated derivative of dynasore, induces more pronounced TMEM175 currents with an estimated EC 50 of 2.3 µM [88]. Following the removal of dynasore chemicals, TMEM175 currents rapidly decreased, indicating the utilization of an effective internalization mechanism to translocate TMEM175 proteins from the plasma membrane to intracellular organelles.…”
Section: Regulation Of the Tmem175 Channel Activitymentioning
confidence: 99%
“…Additionally, the heterologous expression of mouse TMEM175 in Xenopus laevis oocytes results in very small currents through the plasma membrane of oocytes. Dynasore compounds, which are potent dynamin inhibitors and disrupt clathrin-dependent endocytosis, have been reported to control the cellular localization of TMEM175 proteins [88]. TMEM175 currents in the plasma membrane were greatly increased in the cells treated with dynasore, with an estimated EC 50 of at least 30 µM [88].…”
Section: Regulation Of the Tmem175 Channel Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, surface expression of intracellular transport proteins upon manipulation of sorting/internalization signals represents a powerful tool for their functional characterization, which in some cases even was the only successful approach so far. There is also one report, in which the use of inhibitors of dynamin redirected the lysosomal K + channel c to the plasma membrane upon expression in Xenopus oocytes [112].…”
Section: Targeting To the Plasma Membrane Upon Manipulation Of Sortin...mentioning
confidence: 99%